Seedlings Quality of Rain Tree, Balsa, and Soursop in The BPDAS Permanent Nursery, Solo - Nufus, Malihatun; Widodo, Tulus (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
The quality of seedlings reflects of the genetic and physiological quality of plants. Good seedlings are an important factor in the success of planting. This study aimed to assess the quality of seedlings produced at the BPDAS Solo Permanent Nursery. The assessment of seedling quality criteria is based on the Regulation of the Director General of RLPS Number P.05/V-SET/2009 and SNI 8420:2018. Three species of seedlings are assessed, namely trembesi, balsa, and soursop. The origin of the seeds of the 3 species of seedlings tested did not come from a certified seed source or had seed quality information so they had not passed the test for the seed origin criteria. The physical quality requirements for seedlings include the percentage of normal seedlings and the average of special requirements for the three species of seedlings tested in the category of passing the test and first quality (P). This showed that BPDAS Solo Permanent Nursery produces seedlings that meet standards and are ready to be planted in the field. Keywords: seedling quality, raintree, balsa, soursop, permanent nursery